Synthesis of titania-bentonite nanocomposite and its applications in water-based drilling fluids - Nizamani, A.A. (Italian Association of Chemical Engineering - AIDIC, 2017)
Titania or TiO2-bentonite nanocomposite was synthesised by environmental friendly and cost effective hydrothermal method. Synthesised nanocomposite was successfully characterised by Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD). The target of the study was to enhance the rheological behaviour of the water-based drilling fluid (WBDF) by using synthesised nanocomposite. The experimental results revealed that Titania-bentonite nanocomposite exhibited better rheological characteristics than conventional WBDF. Rheological properties in particular yield point (YP) and 10-min gel strength (10-min GS) were improved by 57 and 40 compared to basic drilling fluid after addition of 1.0 g of the synthesised nanocomposite at 65.56 °C. API filtrate loss volume and High Pressure High Temperature (HPHT) filtrate loss volume were slightly reduced by 10 , and 9.2 . These scientific results can be used to formulate enhanced WBDF at elevated temperatures. Copyright © 2017, AIDIC Servizi S.r.l..